Features of technological synthesis and properties of ZnO-Cd based materials for photocatalytic applications. Review - Didus, R. I.; Myroniuk, D. V.; Myroniuk, L. A.; Ievtushenko, A. I. (Physics and Chemistry of Solid State, 2023)
In this review, the current state of ZnO-Cd based materials for photocatalytic applications is summarized. Relevant technological synthesis methods such as pulsed laser deposition, magnetron sputtering, electrodeposition, sol-gel, metalorganic chemical vapor deposition, evaporating, spray pyrolysis, reflux are considered, and recent developments in effective and reproducible synthesis technology of nano- and microstructured zinc oxide, doped with cadmium and solid solutions of Zn1‑xCdxO for photodecomposition of organic pollutant molecules are discussed. The synthesis technology and level of Cd doping has a significant effect on the structure and morphology of zinc oxide and, as a result, on the optical and photocatalytic properties. The figures of merit, the theoretical limitations and rational control of the concentration of the cadmium alloying impurity is necessary to create a material with balanced optical properties and photocatalytic activity. Lastly, the importance of doping ZnO by isovalent Cd impurity significantly improves its photocatalytic properties due to a narrowing of the band gap, a decrease in the rate of recombination of electron-hole pairs, which increases the efficiency of spatial charge separation, the formation of active oxide radicals and an increase in the specific surface area. Thus, ZnO-Cd based materials are the most promising photocatalytic materials for organic pollutants.